Social-Cultural Factors and School Dropout Among Girls in Secondary Schools of Industrial Division (Mbale District) - Leah Nadunga (Uganda Christian University, 2024)
This study examines the social-cultural factors leading to school dropout among girls in secondary schools in the Industrial City Division of Mbale District. The research aimed to identify the cultural norms, social dynamics, and patriarchal influences affecting girls' educational persistence. Data were collected using a combination of quantitative and qualitative methods, including questionnaires, purposive interviews, and surveys. The sample comprised parents, teachers, head teachers, and students, selected through simple random and purposive sampling techniques. The findings highlight that gender stereotypes, early marriage, pregnancy, socioeconomic status, and parental attitudes significantly impact girls' school retention. To address these issues, the study recommended enhancing gender equality policies, increasing community awareness about early marriage, providing socioeconomic support, promoting supportive parental attitudes, and improving school guidance services. Future research should investigate regional differences in gender stereotypes, socioeconomic factors, parental attitudes, and resource availability to further understand their effects on girls' educational outcomes.
Undergraduate Research